Determinants of audit fees: Evidence from Poland - Karol Rewczuk; Piotr Modzelewski (Central European Economic Journal (CEEJ), 2019)
Unlike many studies concerning audit fees in Western Europe or the United States, literature concerning this kind of research is very limited in Central and Eastern Europe. This study aimed to show what factors shape audit fees in Poland. It was conducted based on data collected from the financial statements of 111 companies listed on the Warsaw Stock Exchange in 2018. The study used a linear regression model to verify the determinants of audit fees. The research results indicate a positive relationship between audit fees and company size, measures of complexity (in addition to the ratio of inventories and receivables to total assets) and the fact that a company is audited by the 'Big Four' accounting firms.
Keywords: M42; M48; 330; audit fee; statutory auditor; accounting; Warsaw Stock Exchange